THE INFLUENCE OF BRAND AMBASSADOR AND BRAND IMAGE ON PURCHASE DECISIONS IN TOKOPEDIA E-COMMERCE - Gracela Sarah Fanuel; Supriyono Supriyono (International Journal of Economy, Education and Entrepreneurship, 2023)
In the digital era and advances in information technology, e-commerce has become a form of trade that is very popular and dominates the market. Consumers are increasingly turning to e-commerce platforms to purchase products and services online. In the increasingly fierce competition in the e-commerce market, companies must build a strong brand image and influence consumer purchasing decisions. This study explores the influence of brand ambassadors and brand image on purchasing decisions on the Tokopedia e-commerce platform. This study used a quantitative approach to collect the required data. Questionnaires were distributed to 100 respondents to collect the data needed in this study. The results of the study show that the brand ambassador variable has a significant impact on the respondents' purchasing decisions. In this context, transference from brand ambassadors has the most decisive influence among the other indicators considered. It shows that when consumers see brand ambassadors they like or trust, they are more likely to make profitable purchasing decisions for Tokopedia